Imaging‐guided cardiac resynchronization therapy: A meta‐analysis of randomized controlled trials. Issue 9 (21st July 2021) - Kheiri, Babikir; Przybylowicz, Ryle; Simpson, Timothy F; Merrill, Miranda; Osman, Mohammed; Dalouk, Khidir; Rahmouni, Hind; Stecker, Eric; Nazer, Babak; Henrikson, Charles A.
Abstract: Background: Among patients with heart failure and left ventricular (LV) dysfunction despite guideline directed medical therapy, cardiac resynchronization (CRT) is an effective technology to reverse LV remodeling. Given that a large portion of patients are non‐responders, alternatives to traditional LV‐lead placement have been explored. A promising alternative is image targeted placement of an LV‐lead to latest mechanically activated segment without scar. Methods: Electronic database search for randomized controlled trials (RCTs) that evaluated the imaging‐guided LV‐lead placement on clinical, echocardiographic, and functional outcomes. The primary outcome was a composite of mortality and heart failure hospitalization. The secondary outcomes included CRT responders, New York Heart Association (NYHA), 6‐minute walk test, Minnesota Living with Heart Failure Questionnaire (MLHFQ), and ejection fraction (EF) changes. Results: Analysis included 4 RCTs of 691 patients with an average follow‐up of 2 years (age 69.5 ± 10.3 years, 76% males, 54% ischemic cardiomyopathy, 81% with NYHA classes III/IV, and EF of 24.4% ± 8). The most common site for LV‐lead paced segment was the anterolateral segment (45%) and at mid‐LV (49%). Compared with the control, imaging‐guided LV‐lead placement was associated with a significant reduction of the primary outcome (hazard ratio [HR] = 0.60; 95% CI = 0.40–0.88; p = .01), higher CRT responders (odd ratio [OR] = 2.10; p < .01), more NYHA improvements by ≥1 (OR = 1.89; p = .01), increased 6MWT (mean difference [MD] = 25.78 feet; p < .01), and lower MLHFQ (MD = ‐4.04; p = .04), without significant differences in the LVEF ( p = .08). Conclusions: In patients undergoing CRT, imaging‐guided LV‐lead placement was associated with improved clinical, echocardiographic, and functional status.